(7-Chloroquinolin-4-yl)arylhydrazones: Candida albicans enzymatic repression and cytotoxicity evaluation, Part 2. (2nd January 2016) - de Azambuja Carvalho, Pedro Henrique; Duval, Auri Rocha; Manzolli Leite, Fabio Renato; Nedel, Fernanda; Cunico, Wilson; Lund, Rafael Guerra
Abstract: Objective : This work describes the anti-enzymatic activity of (7-chloroquinolin-4-yl)arylhydrazones against Candida albicans and examines their cytotoxicity. Material and methods : Ten C. albicans strains [nine isolates and one azole-resistant standard strain (ATCC 62342)] were used to assess the anti-enzymatic activity. Fifteen compounds at sub-antifungal concentrations ranging from 12.5 to 100 µg/ml were assessed after a 30-min exposure. The strains were seeded onto petri dishes with selective agar media for aspartyl proteases (Saps) and phospholipases (PLs). Enzymatic inhibition was measured by the reduction of the precipitation zone (Pz) against untreated strains (positive control). A colorimetric MTT assay was used with 3T3/NIH mouse fibroblasts to evaluate cytotoxicity. Cells were exposed to 15 compounds in concentrations from 6.25 to 100 µg/ml for 24 and 48 h. Results : Four hydrazones showed enzymatic repression values over 40% to Pl and three over 20% to Saps. The cell viability was over 50% at hydrazone concentrations of 25–100 µg/ml. Conclusion : These results revealed that select (7-chloroquinolin-4-yl)arylhydrazones may be potential antifungal agents for the control of C. albicans infections.